Service‐user experiences of an integrated psychological intervention for depression or anxiety and tobacco smoking in improving access to psychological therapies services: A qualitative investigation into mechanisms of change in quitting smoking - Kim Fredman Stein; Katherine Sawyer; Shadi Daryan; Jennifer Allen; Gemma Taylor (Wiley, 2023)
Abstract Introduction High smoking prevalence leads to increased morbidity and mortality in individuals with depression/anxiety. Integrated interventions targeting both smoking and mood have been found to be more effective than those targeting smoking alone, but the mechanisms of change of these interventions have not been investigated. This qualitative study aimed to understand participants' experiences of the mechanisms underlying change in smoking behaviour following an integrated cognitive behavioural technique‐based intervention for smoking cessation and depression/anxiety. Methods This study was embedded within an ongoing randomized‐controlled acceptability and feasibility trial (http://www.isrctn.com/ISRCTN99531779). Semistructured interviews were conducted with 15 IAPT service users. Data were analysed using thematic analysis. During the interviews, participants were asked open‐ended questions about their quitting experience and perception of how the intervention aided their behaviour change. Results Five themes were identified. Acquiring an increased awareness of smoking patterns: participants described an increased understanding of how smoking was contributing towards their mental health difficulty. Developing individualized strategies: participants described acquiring 'a couple of tricks up your sleeve' that were helpful in making smoking cessation feel more 'manageable'. Practitioner style as 'supportive but not lecture‐y': participants expressed how important the therapeutic alliance was in helping change their smoking behaviour. Importance of regular sessions: participants expressed the importance of 'having someone that's checking in on you'. Having the opportunity to access the intervention at 'the right time': participants described the intervention as the 'push' that they 'needed'. Conclusions Participants identified key factors towards smoking behaviour change. Perceived increased awareness of how smoking negatively impacted participants' mental health, and the opportunity to be offered smoking cessation treatment in a 'non‐judgemental', 'supportive' environment, with regular sessions and individualized strategies contributed to successful smoking cessation outcomes. If similar results are found in more diverse samples, these aspects should be embedded within integrated interventions for smoking cessation and depression/anxiety. Patient or Public Contribution Persons with lived experience of depression, anxiety and tobacco addiction contributed towards the design of the interview schedule, participant information sheets and the debriefing process. This was to ensure that interview questions were relevant, nonjudgemental and acceptable for those who did not manage to quit smoking.